Socialization of aquaponics utilization technology and aricultural waste as growing media for food security in Limporilau Village, Wajo Regency - Putri, Harmin Adijaya; Rosadi, Sri Hardianti; Purnamasari, Fitry; Nurjaya, Nurjaya (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2023)
The community service activity in Limporilau Village revealed that there is a problem regarding the low level of knowledge among the community about the utilization of aquaponics technology. Many people are still unaware that aquaponics can be implemented in limited spaces such as home gardens. The method used to address this issue includes socialization, lectures, discussions, and training on aquaponics system construction. The results obtained from these activities showed an improvement in the community's knowledge of aquaponics. This initiative aims to enhance food security and the self-reliance of the community. By utilizing aquaponics, which combines plant cultivation and fish farming, the community can benefit from a single system. Aquaponics also offers an alternative business opportunity for the community, as it yields high-value organic plants and fresh fish.